Research strengths and future perspectives on fiber reclamation of reinforced polymers. (November 2021) - Gagliardi, F; Conte, R; Ambrogio, G
Polymers constitute the most employed reinforced matrices to achieve composite materials. Carbon and glass fibers are the reinforcements that are mainly utilized to improve specific properties for both thermoplastics and thermosets creating a new class of materials, which has been applied in several industrial fields. Various products made of fiber reinforced polymers are available on the market and at their own end-of-life, they must be reclaimed and remanufactured, properly, in an ideal recycling circular economy. The aim of this review is to point out the progress on fiber reclaiming from these materials, providing an overview on the most employed strategies and highlighting their main technological limits. Specifically, first, mechanical, thermal and chemical reclaiming processes have been contextualized introducing their peculiarities. Subsequently, the attention has been focalized on the new research trends proposed in the last years showing the direction, where the research is moving to. The processes have been also classified in terms of tensile strength of the reclaimed fibers and in terms of the energy required to be performed. Finally, design for reclaiming and remanufacturing treatments have been also considered pointing out the different approaches that can be pursued as valuable solutions to strengthen the recycling capabilities encouraging as much as possible the recovering of the polymeric matrix composites.